**Answer:**

GE = 14

**Step-by-step explanation:**

The incenter is equidistant from the sides, so GD = GE = GF.

Set the expressions for GD and GF equal to each other and solve for x.

3x + 5 = 6x - 4

5 = 3x - 4

9 = 3x

3 = x

Now plug this value into either expression, say for GD. GD = 3(3) + 5 = 14.

GE must be the same, GE = 14

**Answer:**

36

**Step-by-step explanation:**

45*(9/5)=81(The whole score)

81-45=36(the second half score)

For this case we have the following expressions:

x-3

Y

Adding both expressions we have:

(x-3) + (y)

Rewriting we have:

x - 3 + y

y + x - 3

**Answer:**

**The sum of the quantity x-3 and y is:**

**y + x - 3**

**Answer:**

358

**Step-by-step explanation:**

**Answer:Your answer would be C have a good day reach out to me if u need more help**

**Step-by-step explanation:**